2015
DOI: 10.1371/journal.pone.0141006
|View full text |Cite
|
Sign up to set email alerts
|

Discrimination of Deciduous Tree Species from Time Series of Unmanned Aerial System Imagery

Abstract: Technology advances can revolutionize Precision Forestry by providing accurate and fine forest information at tree level. This paper addresses the question of how and particularly when Unmanned Aerial System (UAS) should be used in order to efficiently discriminate deciduous tree species. The goal of this research is to determine when is the best time window to achieve an optimal species discrimination. A time series of high resolution UAS imagery was collected to cover the growing season from leaf flush to le… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

10
101
2
4

Year Published

2017
2017
2022
2022

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 103 publications
(117 citation statements)
references
References 28 publications
10
101
2
4
Order By: Relevance
“…Previous UAV-based studies have been based on only multispectral data captured using NIR-modified cameras. Lisein et al [41] performed classification using RandomForest and achieved an overall classification error of 16% (out of bag error) with five different tree species. Michez et al [39] achieved a classification accuracy of 84% with five different tree species but the results were closer to pixel-based classification where a single tree was not represented as a whole.…”
Section: Consideration Of Identification and Classification Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Previous UAV-based studies have been based on only multispectral data captured using NIR-modified cameras. Lisein et al [41] performed classification using RandomForest and achieved an overall classification error of 16% (out of bag error) with five different tree species. Michez et al [39] achieved a classification accuracy of 84% with five different tree species but the results were closer to pixel-based classification where a single tree was not represented as a whole.…”
Section: Consideration Of Identification and Classification Resultsmentioning
confidence: 99%
“…Multispectral data Remote Sens. 2017, 9, 185 3 of 34 acquired from UAVs has been used in tree species classification, but the data has been limited to RGB images and one near-infrared (NIR) channel using NIR-modified cameras [39][40][41]. The development of low-weight hyperspectral imaging sensors is likely to increase the use of spectral data collected from UAVs in forestry applications [34].…”
Section: Introductionmentioning
confidence: 99%
“…3). Some of the high volume stands had large deciduous stem volume and Q2 images were acquired during leaf-off season, this affect the image matching to generate points mostly on the ground and with more noise and thus the canopy height metric values negatively Lisein et al 2015;Bohlin et al 2015), clearly underestimating raster cells with high deciduous proportion. Another reason for underestimation is that the mature stands, which are under estimated (Fig.…”
Section: Discussionmentioning
confidence: 99%
“…They claimed that UAV flights with short time intervals can refresh LiDAR CHMs in order to create canopy height series. Lisein et al (2015) reported classification of deciduous trees with UAV imagery with high classification accuracy. Zhang et al (2016) showed that long-term ecological monitoring can be effectively done by UAV systems with high resolution data.…”
Section: Introductionmentioning
confidence: 99%